Exploring how Grade 9 Physical Science teachers mediate learning of the topic of chemical changes - Likando, Orrice Munukayumbwa (Rhodes University, Faculty of Education, Department of Education)
The examiners' reports for 2013-2018 indicated that learners consistently perform poorly in questions based on chemical changes. My assumption is that the reason why learners are challenged with understanding the topic of chemical changes could be due to the way this topic is taught. It is against this background that this study explored how grade 9 Physical Science teachers mediated learning of the topic of chemical changes. The study is underpinned by an interpretive paradigm. Within the interpretive paradigm, a qualitative case study research design was employed. It was conducted at two different schools in the Otjozondjupa region with two Physical Science teachers. Data were collected using semi-structured interviews, lesson observations, stimulated recall interviews, and teachers' reflections. The study is informed by Vygotsky's socio-cultural theory together with Shulman's pedagogical content knowledge as the theoretical frameworks. A thematic approach to data analysis was adopted. That is, qualitative data were analysed inductively to come up with sub-themes to form themes. Moreover, validation and trustworthiness were completed through data triangulation, member checking, and watching videotaped lessons with the participants. The findings of this study revealed that the topic of chemical changes has many examples which can be used during mediation. Teachers seemed to be aware of integrating learners' experiences into their lessons. Furthermore, they were aware that they should improvise resources during mediation of learning. In contrast, during lesson observations, the findings revealed an imbalance between this awareness and the actual knowledge of using easily accessible materials, and the elicitation and integration of prior knowledge throughout the science lessons. Moreover, hands-on practical activities were lacking in the mediation process and instead, traditional methods of teaching tended to dominate. Nonetheless, teachers' reflections influenced them to analyse and strengthen their lessons. Thus, the study recommends that there is a need for teachers to have mentorships and platforms which can expose them to the knowledge of different types of easily accessible materials. This might strengthen their PCK. Teachers are also encouraged to do some reflections after very lesson as these have a potential to influence their pedagogical practices.
Keywords: Science -- Study and teaching (Secondary) -- Namibia; Chemistry -- Study and teaching (Secondary) -- Namibia; Culturally relevant pedagogy; Pedagogical content knowledge; Prior learning -- Namibia